RECOGNITION OF THE OTHER FOR THE EFFECTIVE WORK OF THE REHABILITATION NURSE: AXEL HONNETH REFERENCE - Diana Raquel Meireles Pinto; Olga Maria Pimenta Lopes Ribeiro; Maria Manuela Ferreira Pereira Da Silva Martins; Soraia Dornelles Schoeller (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objective: to reflect on the potential of the Theory of Recognition for the professional practice of rehabilitation nurses. Method: reflective theoretical study based on the framework of Axel Honneth and the specific skills of rehabilitation nurses. Results: two analysis topics emerged - the theoretical framework of Axel Hornet; and the contribution of Axel Honneth's theoretical framework to the professional practice of rehabilitation nurses. Discussion: the support of professional practice in theoretical frameworks has been deeply defended in the last decade, and in this context, Axel Honneth makes a significant contribution to the intentional and systematic performance of the rehabilitation nurse. Conclusion: during the rehabilitation process, in addition to the importance of recognizing the person, it was clear that in the context of the therapeutic relationship, the rehabilitation nurse must attend to the three pillars presented by Honneth, love, right and solidarity, so that the person be completely respected.